“The teeth which are together are the ones which bite the most”: Sensemaking, interpersonal ranger relations, and organisational identification in Ugandan protected areas - Moreto, William D. (International journal of comparative and applied criminal justice, 2022)
While wildlife law enforcement has received considerable research interest in recent years, little attention has been given to interpersonal relationships between junior rangers and their supervisors in protected areas. Based on 89 semi-structured interviews with rangers in Uganda, the present study explores interpersonal relations between juniors and their supervisors, and the impact this dynamic has on sensemaking and organisational identification. Findings suggest that study participants considered communication, mentorship, relatability, and accessibility to be important factors in supporting positive supervisor-junior relations. Factors that hindered relations, included organisational structure and chain of command, operational requirements and decentralised geography of responsibility, inequity, lack of trust, respect, and credibility, as well as retaliation. These factors shape rangers’ sensemaking and the development of their organisational identity. This study has implications for the expansion of criminal justice research on non-traditional, rural forms of enforcement, while also contributing to better understanding the human dimensions of conservation science.